2013
DOI: 10.1103/physrevlett.111.216401
|View full text |Cite
|
Sign up to set email alerts
|

Dirac Cone with Helical Spin Polarization in Ultrathinα-Sn(001) Films

Abstract: Spin-split two-dimensional electronic states have been observed on ultrathin Sn(001) films grown on InSb(001) substrates. Angle-resolved photoelectron spectroscopy (ARPES) performed on these films revealed Dirac-cone-like linear dispersion around the Γ¯ point of the surface Brillouin zone, suggesting nearly massless electrons belonging to 2D surface states. The states disperse across a band gap between bulklike quantum well states in the films. Moreover, both circular dichroism of ARPES and spin-resolved ARPES… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
114
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 36 publications
15
114
0
Order By: Relevance
“…The left-hand panel shows the dispersion along the Γ-X direction (note that due to the dual domain nature of the surface reconstruction in our samples the X and Y points of the surface Brillouin zone (SBZ) can not be distinguished). At 0 eV binding energy we observe a single sharp feature that crosses E F , corresponding to the TSS reported recently 2,3 . In addition, we observe a weak background intensity caused by the projected bulk Γ + 8 band that also crosses E F , revealing a metallic behavior.…”
Section: Electronic Structuresupporting
confidence: 81%
See 2 more Smart Citations
“…The left-hand panel shows the dispersion along the Γ-X direction (note that due to the dual domain nature of the surface reconstruction in our samples the X and Y points of the surface Brillouin zone (SBZ) can not be distinguished). At 0 eV binding energy we observe a single sharp feature that crosses E F , corresponding to the TSS reported recently 2,3 . In addition, we observe a weak background intensity caused by the projected bulk Γ + 8 band that also crosses E F , revealing a metallic behavior.…”
Section: Electronic Structuresupporting
confidence: 81%
“…The low-temperature α-phase of Sn has attracted considerable attention recently as a unique elemental threedimensional topologically non-trivial material [1][2][3][4][5][6][7] . Being a zero-gap semiconductor if unstrained, it can enter a Dirac semimetal or strong topological insulator (TI) phases under strain 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang Fu et al theoretically proposed that such an insulator phase was a strong 3D topological insulator [18]. Two recent experimental studies demonstrated the existence of topological surface states in the valence band regions of -Sn films grown on InSb(001), but no experimental evidence of the strain-induced gap [19,20].…”
mentioning
confidence: 99%
“…Fig. 1 [19] or Bi [20] into Sn films to help films grow smoothly, no such impurity atoms were introduced in our thin film samples yet they were of high-quality. The strain in the 30-BL film was measured by X-ray diffraction using the !…”
mentioning
confidence: 99%